2019
DOI: 10.1590/s1413-65382519000100002
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento da Imaginação e da Criatividade por meio de Design de Games por Crianças na Escola Inclusiva

Abstract: Resumo: Este artigo examina o desenvolvimento da imaginação e da criatividade de crianças com e sem deficiência por meio do design de games. O estudo sustenta-se nas teorias de Vygotski relacionadas à elaboração conceitual, à imaginação e à criatividade na infância e nos estudos avançados em design de jogos com crianças. O Design-Based Research (DBR) foi adotado como abordagem metodológica, configurando pesquisa qualitativa e colaborativa de criação de jogos. Realizaram-se encontros semanais em uma escola da r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…First, several studies reported struggling to achieve agreement on a concept, solution, or decision , likely because of the control each stakeholder group was given [ 42 , 74 , 76 ]. Control in terms of decision-making and contributing to the design process could be caused by expecting CYP to come to a natural agreement without clear constraints or guidance from adults.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, several studies reported struggling to achieve agreement on a concept, solution, or decision , likely because of the control each stakeholder group was given [ 42 , 74 , 76 ]. Control in terms of decision-making and contributing to the design process could be caused by expecting CYP to come to a natural agreement without clear constraints or guidance from adults.…”
Section: Resultsmentioning
confidence: 99%
“…Common approaches to this issue were discussion (for understanding different points of view) and voting mechanisms (for integrating disagreeing points of view into a decision) [ 76 ]. A connected challenge was ensuring that different end-user groups contributed more or less equally to decisions and end results [ 42 , 50 , 64 , 65 ]. Several authors observed that cohesion required trust between participants, although no particular approach has been suggested to build trust [ 42 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations